Challenges for University Teaching from the Pedagogy of Autonomy - Valdivia Durán, Stephanie (2019)
Costa Rican high school education is stagnant in terms of quality due to a prevailing traditional educational model. Based on this, a student’s profile that enrolls at the university can be defined by an individual without personal opinion and lack of responsibility for his or her educational process. In order words, this student is not educated for his or her autonomy. For this reason, university teaching faces the challenge to foster autonomy processes in the students, in order to let them find in the university the space to develop personally and professionally. One of the pedagogical challenges happens mainly with first-year students, as they do not come prepared with certain necessary skills for university life; it is the professor who strengthens those abilities. One of the main tasks is found in pedagogical mediation. For this reason, this essay aims to address four specific aspects that university teachers should face to perform a pedagogical praxis focusing their mediation on Freire’s Pedagogy of Autonomy.